2016
DOI: 10.1080/21541248.2016.1215658
|View full text |Cite
|
Sign up to set email alerts
|

Formin-mediated epigenetic maintenance of centromere identity

Abstract: Accurate chromosome segregation in mammalian cells is guided by the centromere, a specialized chromosome region defined by the histone H3 variant centromere protein A (CENP-A). It is not well understood how cells maintain CENP-A levels at centromeres while continuously going through genome replications and cell divisions. A MgcRacGAP-dependent small GTPase molecular switch has been shown as essential for centromeric CENP-A maintenance. By using quantitative imaging, pulse-chase and live cell analysis, a recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…XPA roles in cell cycle progression were observed by the downregulation of the XPA-binding protein 2 (XAB2) affecting the transcription of mitotic related genes, including the centrosome-associated gene E (CENP-E) (Hou et al, 2016). On the other hand, Rho pathway is related to centrosome organization through the effector mDia2 by maintaining the correct levels of CENP-A at the centrosomes (Liu and Mao, 2017), therefore highlighting a potential correlation between Rho pathway and XPA protein, even independently of NER pathway, thus contributing for the understanding of cellular responses reported here. Indeed, Rho LoF is still able to increase sensitivity of NER-deficient cells to UV radiation effects by elevating the levels of DNA fragmentation and accumulation of CPD lesions (Figures 6, 7 and Supplementary Figures 6, 7).…”
Section: Discussionmentioning
confidence: 99%
“…XPA roles in cell cycle progression were observed by the downregulation of the XPA-binding protein 2 (XAB2) affecting the transcription of mitotic related genes, including the centrosome-associated gene E (CENP-E) (Hou et al, 2016). On the other hand, Rho pathway is related to centrosome organization through the effector mDia2 by maintaining the correct levels of CENP-A at the centrosomes (Liu and Mao, 2017), therefore highlighting a potential correlation between Rho pathway and XPA protein, even independently of NER pathway, thus contributing for the understanding of cellular responses reported here. Indeed, Rho LoF is still able to increase sensitivity of NER-deficient cells to UV radiation effects by elevating the levels of DNA fragmentation and accumulation of CPD lesions (Figures 6, 7 and Supplementary Figures 6, 7).…”
Section: Discussionmentioning
confidence: 99%
“…These factors include the Rho GTPase MgcRacGAP, the formin protein mDia, and the RSF-1 remodeling complex, and appear to be recruited to centromeres later than Mis18 and HJURP (Fig. 1) (Izuta et al 2006; Lagana et al 2010; Liu and Mao 2016; Obuse et al 2004; Perpelescu et al 2009). …”
Section: Centromere Stabilization and Re-organizationmentioning
confidence: 99%
“…The constitutively active form of mDia2 restores CENP-A levels at the centromere resulting from MgcRacGAP downregulation, consistent with its role downstream of MgcRacGAP in this process. Interestingly, mDia2 depletion leads to prolonged HJURP association with the centromere, suggesting that the processes of HJURP recruitment and MgcRacGAP stabilization are mechanistically linked (Liu and Mao 2016). …”
Section: Centromere Stabilization and Re-organizationmentioning
confidence: 99%
“…The diaphanous formin (mDia) proteins are important small Rho GTPase effectors and can regulate cytoskeletal dynamics by stabilizing microtubules and nucleating filamentous actin in a linear fashion ( Chesarone et al., 2010 ). Previously we have reported that formin mDia2 is required for maintaining CENP-A levels at the centromere ( Liu and Mao, 2016 , Liu and Mao, 2017 ). Importantly, overexpressing a constitutively active form of mDia2 can rescue defective centromeric CENP-A levels caused by depleting MgcRacGAP.…”
Section: Introductionmentioning
confidence: 99%